2006
DOI: 10.1161/01.str.0000249008.18669.5a
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Inhibits Subarachnoid Hemorrhage–Induced Inducible Nitric Oxide Synthase Gene Expression by Interfering With the Nuclear Factor κB Transactivation

Abstract: Background and Purpose-Previously, we showed that 17␤-estradiol (E 2 ) treatment prevented the subarachnoid hemorrhage (SAH)-induced cerebral vasospasm in male rats. The aim of this study was designed to further delineate the molecular mechanisms underlying E 2 -induced inhibition of inducible nitric oxide synthase (iNOS) upregulation and relief of vasospasm caused by SAH. Methods-The 2-hemorrhage SAH model was induced by 2 autologous injections of blood into the cisterna magna of adult male rats. The rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 28 publications
3
30
1
Order By: Relevance
“…The nuclear transcription factor NF-κВ has been shown to be an important inflammatory mediator in brain tissue during the pathophysiological occurrence of cerebral vasospasm (35). NF-κВ is mainly expressed in vascular endothelial cells and cell nuclei of the outer membrane, and its expression level is positively correlated with the degree of vascular spasm (36).…”
mentioning
confidence: 99%
“…The nuclear transcription factor NF-κВ has been shown to be an important inflammatory mediator in brain tissue during the pathophysiological occurrence of cerebral vasospasm (35). NF-κВ is mainly expressed in vascular endothelial cells and cell nuclei of the outer membrane, and its expression level is positively correlated with the degree of vascular spasm (36).…”
mentioning
confidence: 99%
“…Furthermore, because of the association of p65 with the estrogen receptor, 17β-estradiol blocked the binding of p65 to the gene target inducible NOS (iNOS). Therefore, this hormone drug reduced iNOS and showed a neuroprotective effect on CVS [57]. The activation of NF-κB was biphasic in a single injection rabbit SAH model.…”
Section: The Functional Alteration Of Organelles Within the Progressimentioning
confidence: 99%
“…was given for 7 d followed the first hemorrhage. Our previous study showed that pretreatment of the rat with the ICI182,780 (Tocris Bioscience, Ellisville, MO) dose-dependently reversed the E 2 -mediated prevention on the SAH-induced vasospasm with a maximal effect at a dose of 2 mg/kg ICI182,780 [9]. (Tocris) was dissolved in corn oil (Sigma) to make a final concentration of 20% solution.…”
Section: Animal Preparationmentioning
confidence: 99%
“…Accumulating evidence suggests that estrogen affords neuroprotection against brain injury and neurodegenerative diseases both in animal and clinical studies [5,6]. Our previous study showed 17b-estradiol (E2) could attenuate experimental SAHinduced cerebral vasospasm by inhibiting endothelin-1 production [7], preventing the augmentation of iNOS expression by interfering with the nuclear factor k-B transactivation via an estrogen receptor (ER)-dependent mechanism [8,9], and preserving the normal eNOS expression after SAH [8].…”
Section: Introductionmentioning
confidence: 99%